Research trends in environmental information disclosure: A bibliometric analysis - Thuy An Nguyen; Senthil Kumar; Shahryar Sorooshian (CTU Journal of Innovation and Sustainable Development)
This study aimed to investigate the development of environmental information disclosure (EID) research publications from 1992 to 2024 to identify trends and provide valuable insights to researchers in related fields. This study employed performance analysis and science mapping strategies, utilizing VOSviewer software and the Biblioshiny function within the R package software, to achieve its research objectives. The results reveal a gradual growth in the number of citations and published publications related to EID topics, and this trend is projected to continue in the upcoming years. The journal "Sustainability" has the most papers, but "Journal of Cleaner Production" has the most citations. Li, Y., Yang, Y.L. and Yao, S. are the most productive authors in terms of number of publications, however, Zeng, S.X., Garcia-Sanchez, I.M. and Gallego-Alvarez, I. are recognized as having papers ranked in the H-index and G-index, respectively. In addition, thematic map analysis indicates terms in two groups, including Niche and Motor themes should be the focus key terms of future research. Additionally, the results indicate that environmental, social, and governance (ESG) performance, digital transformation, EID, and green innovation are among the top topics in terms of research trends for recent three years (2022-2024). This study suggests several potential future research directions by examining the relationship between these terms in different countries and industries.